PENGARUH DEBT TO EQUITY RATIO, RETURN ON EQUITY DAN CURRENT RATIO TERHADAP NILAI PERUSAHAAN - Agustine, Jessica Anggraini; Setiawan, Veronica (Fakultas Ekonomi, Bisnis dan Humaniora, 2024)
A high firm’s value gives an idea that the company’s shares are also high. This will be attractive and well viewed by investors. PT Japfa Comfeed Indonesia. Tbk has a firm value that is still relatively high, but the company’s debt is increasing and the results of previous research are different from the results of data on the company. This research aims to examine the effect of Debt to Equity Ratio, Return on Equity, Current Ratio on Firm Value. The population in this study is industrial companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. The data used are secondary data. Based on the purposive sampling method there are 29 companies final samples from this study. Observations were made for 4 years so that the number of observations obtained was 116 observation data. The analytical method used is multiple linear regression analysis with the help of SPSS 25 application program . The results of this study indicate that Debt to Equity Ratio has a negative effect on Firm Value, Return On Equity has a positive effect on Firm Value and current ratio does not effect on Firm Value